Enhancing Universal Dependency Treebanks: A Case Study - Joakim Nivre; Paola Marongiu; Filip Ginter; Jenna Kanerva; Simonetta Montemagni; Sebastian Schuster; Maria Simi (My University, 2022)
We evaluate two cross-lingual techniques for adding enhanced dependencies to existing treebanks in Universal Dependencies. We apply a rule-based system developed for English and a data-driven system trained on Finnish to Swedish and Italian. We find that both systems are accurate enough to bootstrap enhanced dependencies in existing UD treebanks. In the case of Italian, results are even on par with those of a prototype language-specific system.
Proceedings of the Second Workshop on Universal Dependencies (UDW 2018)